INDOOR ENVIRONMENTAL QUALITY ASSESSMENT IN A LEARNING SPACE: UNIVERSITY OF MALAYA’S MAIN LIBRARY - Mahyuddin, Norhayati; Law, Jun Bien (Journal of Surveying, Construction and Property, 2019)
The open space concept in the modern library invokes a feeling of approachability and socialization. These open spaces are favourably designed for different usages such as individual study, group discussion, computer or laptop usage, and leisure activities. Nevertheless, questions arise whether or not these designated areas provide enough personal comfort regarding indoor environmental quality (IEQ). Are these areas equipped with good furniture layout, acoustic design features, lighting fixtures, and a mechanical ventilation system for the comfort of users? Thus, this study is to identify, evaluate, and compare different designated open space zones or areas in terms of personal comfort, perceived productivity, and health symptoms related to indoor environmental quality. The study reveals that the occupants are neither easily disturbed in terms of perceived productivity nor susceptible to any health symptoms. However, any approach to open space zoning or ergonomic adjustment has to be incorporated with measures correlated with IEQ elements in order to provide a more productive, conducive and comfortable environment.